A NEGOTIATING GENDER AND CULTURE: A SEMIOTIC ANALYSIS OF ANGGINI'S COSTUME IN WIRO SABLENG 1995 AND 2018 - Puspitasari, Feny; Piliang, Yasraf Amir; Kahdar, Kahfiati; Waskita, Dana (Home Economics Journal, 2025)
Different cinematic contexts reflect filmmakers' varied perspectives and intentions, shaping the visual ideologies presented on screen. One principal means by which filmmakers articulate such ideologies is through costume design. Costumes function not merely as clothing but as symbolic artefacts that convey social, cultural, and ideological meanings. They play a vital role in shaping audience perceptions of characters and their roles while revealing more profound insights into identity, values, and worldviews. Previous research has highlighted how costumes contribute to character identity, particularly in terms of status, role, and psychological attributes. This study employs Roland Barthes’ semiotic theory and content analysis to explore the denotative and connotative meanings of costumes. The aim is to deepen the understanding of costume as a visual medium and to examine its ideological function, particularly in character representation. The analysis focuses on the character Anggini in the Wiro Sableng series (1995) and the movie (2018). Findings indicate that Anggini’s costume in the 1995 series reflects traditional cultural values, emphasising modesty, elegance, and femininity. In contrast, the 2018 film's costumes portray female strength more explicitly, influenced by Western aesthetics and the film’s multinational context. A structural costume pattern for female warrior characters typically consists of traditional female attire on the upper body, accompanied by male or unisex garments below for enhanced agility, and functional footwear for combat. These findings offer practical insights for emerging costume or fashion designers working with female warrior archetypes in Indonesian cinema.